REFORMASI BIROKRASI DALAM ASPEK EFISIENSI DAN TRANSPARANSI PADA PELAYANAN BIROKRASI PEMERINTAHAN KOTA BATU - Tobby Putra Kusuma; Dava Surya Setyadi; Ivan Wisnu Andaru; Ali Roziqin (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2022)
Government bureaucratic reform is a part and effort to strengthen the state because through bureaucratic reform the role of government is redefined to answer challenges, because bureaucratic reform does not just simplify the bureaucratic structure but can change the mindset and pattern of bureaucratic culture for various roles in governance. Bureaucratic reform in Batu City has been regulated in Batu Mayor Regulation No. 58 of 2020. This regulation is a form of Batu city planning to make improvements in the bureaucratic system. The purpose of this study was to determine the performance and process of running administrative bureaucratic services in the Batu City Government. Efficiency in administrative services in the city of Batu is still far from being effective. This is especially so that all services and licensing offices that are all in one place should be able to process permits faster. This seems not to be used by the Batu city government.